Improving Activities and Learning Outcomes of Class VIII Students.C SMP Negeri 2 Kendari in Islamic Religious Education Subjects Through Team Teaching Strategy - Marwah (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2022)
This study aims to determine how team teaching strategies in Islamic Religious Education learning can increase the activities and learning outcomes of class VIII.C students of SMP Negeri 2 Kendari. The research was conducted through action research, namely conducting classroom action research with the following stages: 1) planning, 2) implementation, 3) monitoring and evaluation, and 4) analysis and reflection. This research was conducted at SMP Negeri 2 Kendari. The subjects studied were students of class VIII.C SMP Negeri 2 Kendari totalling 35 students with the details 16 males and 19 females. The results obtained in two learning cycles: (1) the results of 10 aspects of observing student activities in the learning process with a total score of 27 with a value of 90 in the second cycle, an increase in value when compared to the first cycle a total score of 13 with a value of 43.33, (2 ) the results of 9 aspects of observing team-teaching activities in learning with a total score of 24 with a value of 88.89 in the second cycle, an increase in value when compared to the first cycle a total score of 17 with a value of 62.96 and (3) the learning outcomes achieved by students showed a very significant increase, wherein the second cycle there was an increase in the value of learning outcomes, where students who obtained an average score of 70 were 31 students (88.57%), an increase in value when compared to the first cycle of students who obtained an average score 70 as many as 21 students (60.00%). Applying the team teaching strategy in learning Islamic Religious Education can increase the activities and learning outcomes of class VIII.C students of SMP Negeri 2 Kendari.